From Civil Rights to Human Rights : Martin Luther King, Jr., and the Struggle for Economic Justice - Jackson, Thomas F. (Book collections on Project MUSE., 2007)
"Drawing widely on published and unpublished archival sources, Jackson explains the contexts and meanings of King's increasingly open call for "a radical redistribution of political and economic power" in American cities, the nation, and the world. The mid-1960s ghetto uprisings were in fact revolts against unemployment, powerlessness, police violence, and institutionalized racism, he argued. His final dream, a Poor People's March on Washington, aimed to mobilize Americans across racial and class lines to reverse a national cycle of urban conflict, political backlash, and policy retrenchment. King's vision of economic democracy and international human rights remains a powerful inspiration for those committed to ending racism and poverty in our time."--BOOK JACKET.